2.11 Covalent Attachment on a Solid Support - Franzini,R. M. (DNA-Encoded Libraries, 2024)
DNA oligonucleotides are polyfunctional molecules, and their various functional groups can interfere with DNA-encoded library synthesis. DNA that is attached to the support used for solid-phase synthesis has functional groups (e.g., exocyclic amines) protected. It is therefore possible to use harsher reaction conditions than would be possible with unprotected DNA, and the use of water-free solvents is also facilitated. For example, amide-bond formation on a solid support tends to be higher yielding than reactions in solution phase.
Keywords: Referencework; DNA-encoded libraries; solid-phase synthesis; on-DNA chemistry; amide-bond formation; protecting groups